The hollow crown. The Wars of the Roses [videorecording (DVD)] - Cooke, Dominic; Cumberbatch, Benedict, 1976-; Bonneville, Hugh; Dench, Judi, 1934-; Gambon, Michael; Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616 (Universal Studios Home Entertainment, 2016)
Henry VI, Parts I and II and Richard III tell the story of an exceptionally turbulent period in British history. These exhilarating and emotionally charged films feature some of Shakespeare's most eloquent and powerful language.